Effectiveness of two common antivenoms for North, Central, and South American Micrurus envenomations - de Roodt, Adolfo R. (2004)
Micrurus snakes (coral snakes) may produce severe envenomation that can lead to death by peripheral respiratory paralysis. Only few laboratories produce specific antivenoms, and despite the cross-reactivity found in some Micrurus species venoms, the treatment is not always effective. To test two therapeutic antivenoms against the venom of four species of Micrurus from Southern America, North of South America, Central America, and North America, the determination of the lethal potency of the venoms, the study of some biochemical and immunochemical characteristics, and the determination of the neutralizing activity of both antivenoms were studied. North American and South American antivenoms neutralized well venoms from Micrurus species of the corresponding hemisphere but displayed lower effectiveness against venoms of species from different hemispheres. It was concluded that the neutralization of Micrurus venoms by regional antivenoms could be useful to treat the envenomation by some Micrurus snakes but is necessary to evaluate carefully the antivenoms to be used with the venoms from the snakes of the region. Also, considering the difficulties for coral snake antivenom production, the development of a polyvalent antivenom is useful to treat the envenomation by coral snakes from different regions is necessary.